SELEKSI DURA ANGOLA DIDASARKAN ANALISIS VARIASI FENOTIPE - Lesmana, Bayu; Setiawan, Kukuh; Hapsoro, Dwi; Asmono, Dwi; Karyanto, Agus (JURNAL AGROTROPIKA, 2025)
Indonesia remains the world’s leading producer of palm oil, contributing substantially to the national economy. Sustaining productivity growth requires the development of superior varieties characterized by high oil yield, reduced trunk height increment, and enhanced oil quality. Dura Angola, a germplasm originating from Africa and introduced by PT Binasawit Makmur in 2010, offers the potential to broaden the narrow genetic base of Dura while providing valuable agronomic traits. This study aimed to identify promising genotypes and select superior Dura Angola populations based on phenotypic variation and genetic parameters. The research was conducted at Mesuji Estate, PT Aek Tarum, South Sumatra, on 1,029 Dura Angola palms planted in 2012. Traits evaluated included yield components (bunch number, fresh fruit bunch weight, average bunch weight), vegetative growth (annual trunk height increment, rachis length, leaf area, frond production), and oil yield components (fruit-to-bunch ratio, mesocarp-to-fruit ratio, oil-to-wet mesocarp ratio, oil-to-bunch ratio, and oil extraction rate). Data were analyzed using an Unbalanced Incomplete Block Design within a General Linear Model framework, followed by estimation of heritability, genetic and phenotypic coefficients of variation, and trait correlations. Significant phenotypic variation was observed for most traits, with high heritability detected in bunch number, fresh fruit bunch weight, rachis length, leaf area, fruit-to-bunch ratio, and oil-to-bunch ratio. Based on the integration of genetic estimates and phenotypic performance, ten elite individuals were identified from accessions A074/20, A040/22, A040/12, A095/05, A041/26, A041/22, and A075/08. These individuals are recommended as potential female parents for introgression with elite Dura lines or to produce commercial D×P hybrids. The utilization of these selected Dura Angola individuals is expected to broaden the genetic base of Dura, improve breeding efficiency, and support the development of superior oil palm varieties for sustainable intensification.